Project-Based Learning (PBL) dalam Perspektif Filsafat Amal Saleh: Pendidikan untuk Aksi Transformatif - Abdillah, Paris; Mustofa, Ahmad; Romadhon, Ahmad; Khoiriyah (Educational Research Center, 2026)
Contemporary education is increasingly required to cultivate learners who are not only cognitively competent but also morally grounded and socially responsible. Project-Based Learning (PBL) has gained prominence as a pedagogical approach that promotes contextual, collaborative, and experiential learning. This article critically examines PBL through the philosophical lens of amal saleh, which conceptualises knowledge as an integrated relationship between understanding, ethical values, and concrete action oriented towards the common good. Employing a conceptual–philosophical literature review, this study analyses scholarly works on PBL, character education, and transformative education. The analysis reveals a strong philosophical convergence between PBL and the concept of amal saleh, manifested through three interrelated dimensions: the epistemic dimension, emphasising reflective and meaningful knowledge construction; the ethical dimension, focusing on the internalisation of moral values and social responsibility; and the transformative action dimension, highlighting the application of knowledge through socially impactful practices. These findings suggest that PBL extends beyond its function as an instructional strategy to operate as a form of educational praxis that integrates knowledge, values, and action. The study underscores the necessity of reinforcing ethical and action-oriented dimensions in educational practice to ensure that learning contributes to equitable and sustainable social transformation.